EFEKTIVITAS KOMITE AUDIT DALAM SUDUT PANDANG AUDITOR INTERNAL - Amalia, Nofa Prima; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the responsibility and the characteristic of audit comittee which has function to improve the effectiveness of the role of audit committee in the perspective of internal auditor. The object of the research is PT Pelabuhan Indonesia III (Persero). This research is qualitative research which uses the primary data inthe form of interview with the informant i.e. the internal auditor and the secondary data is the 2014 documents i.e.: The annual financial statement, the internal audit charter, the decree of dismissal and appointment of the member of the audit committee. The data analysis technique is qualitative descriptive, which is done by collecting, processing and presenting the obtained data so it is easy to be understood. The result of this resarch shows that the role and the responsibility of the audit committee of PT Pelabuhan Indonesia III (Persero) to the financial statement, internal control, internal audit, external audit and the management can be seen from the internal auditor which has been running effectively. The audit committee of PT Pelabuhan Indonesia III (Persero) also has fulfilled the characteristic in the form of strong leadership, independence, competence, meeting, and communication which has function to increase the effectiveness of audit committee. The internal auditor said that the audit committee is very helpful and it has been expected that it will provide input to the related parties to improve the quality of the company.Keywords: Effectiveness, Audit Committee, the Perspective of Internal Auditor.